(untitled) (European Journal of Health Research, 2020)
Considering that, aging is associated with changes that could significantly affect sexuality, and that individuals over 65 years are a group of great sexual heterogeneity, the main purpose of this work is to explore the differences between older men and women in terms of sexual desire, activity, and practices. This study was carried out through a questionnaire survey in order to analyse the differences between the men and women in terms of sexual activity during the past year, sexual desire and practices. Results show us that sexual activity in general, and the type of sexual practice in particular, as well as the frequency of such practices, reflect relevant differences between older women and men. Specifically, results of this work reveal that there are men who acknowledge a greater concern about the decrease in frequency of sexual practices; however, a significantly more pronounced decrease in the frequency of these practices in the past year occurs among women. Although there may be significant differences in some specific sexual practices and in the level of sexual desire and impulse between men and women, a significant number of men and women are sexually active throughout their old age